Impact of Perceived Chronic Social Adversity on the Oral Health Status among Eunuchs in Vishakhapatnam: A Cross Sectional Study (Global Journal of Medical Research, 2022)
Abstract not found
Keywords: eunuchs; social adversity; oral health status; cross cultural adaptation